Artificial Intelligence (AI) Ethics in Fintech and Startup Ecosystems: A Systematic Literature Review Analysis - Aditya Rawasaputra; Rahmat Tullah; I Ketut Sudaryana; Jan Everhard Riworuhi (Institut Teknologi dan Bisnis Bina Sarana Global, 2026)
Artificial intelligence (AI) is reshaping the fintech and startup ecosystem, offering efficiency in credit scoring, fraud detection, investment personalization, and customer service. Yet, its adoption raises pressing ethical challenges, particularly in Indonesia and Southeast Asia. This study conducts a systematic literature review (SLR) using the PRISMA protocol, analyzing over 80 scholarly articles, industry reports, and regulatory documents to examine key ethical issues in AI-driven finance. Findings highlight concerns around algorithmic transparency, data bias, privacy protection, accountability in automated decision-making, and regulatory compliance. Case studies of Indonesian fintech firms reveal emerging best practices, including explainable AI, fairness audits, compliance with the Personal Data Protection Law (UU PDP), and ethics committees. Regulatory frameworks from OJK and international standards such as GDPR and the EU AI Act provide critical guidance, though implementation challenges persist. The review concludes that embedding ethics into AI development lifecycles, strengthening cross-sector collaboration, and enhancing digital literacy are essential to building an inclusive, transparent, and sustainable fintech ecosystem.